The Head of Madrasah’s Strategy in Improving Teacher Performance at MAN 1 Bandar Lampung - Wulan Sari; Reni Dwi Puspitasari; Zulaiha Zulaiha (Journal Corner of Education, Linguistics, and Literature, 2023)
This research aims to determine the increase in teacher performance by the head of the madrasah as the manager of educational institutions at MAN 1 Bandar Lampung, to find out the implementation of conducting an academic supervision program, to find out monitoring and evaluation in supervising the implementation of teaching, follow-up academic supervision. This type of research uses descriptive qualitative research, which will be explained narratively. Observation, interviews, and documentation were carried out for data collection. The research sample was teachers of all subjects at MAN 1 Bandar Lampung. The results of this study indicate that: Improving teacher performance by the madrasah head uses three aspects of the stages starting from planning, implementing and supervising the strategy carried out by the madrasa head in improving MAN 1 Bandar Lampung and fostering teacher performance, providing motivation, providing supervision, and fostering discipline, implementation in carrying out academic supervision programs, and monitoring teacher performance, and monitoring and evaluation in supervising the implementation of teaching, follow-up academic supervision with increased results seen from the results of questionnaires and direct interviews with informants.